Need for Adequate Funding Basic Education for Effective Administration in Nigeria - Ogunode, Niyi Jacob; Hauwa, Audu; Muhammad, Musa (Central Asian Journal of Medical and Natural Science, 2023)
This paper examined the importance of providing adequate funding for basic education for effective administration in Nigeria. The paper adopted a content analysis method to select the kinds of literature used in this paper. The paper used both primary and secondary data. The data were collected from an online publication and print materials. The paper concluded that adequate funding of basic education in Nigeria will lead to; infrastructure facilities development, employment of professional teachers, provision of instructional materials, effective capacity buildings, increment in motivational packages, reduction in education cost and increment in the patronage of basic education. The paper also identified subsidy payment on fuel, corruption, insecurity, a fall in national revenue, revenue leakages and poor access to intervention UBEC funds as factors competing with the budgetary allocation of the educational sector (basic education) in Nigeria.